Economic diplomacy in the context of great power competition for influence over global trade systems - Chopenko, Darya (Здобутки економіки: перспективи та інновації, 2026)
The study’s relevance stems from the intensification of geoeconomic competition among leading states, driven by regulatory instability and the gradual fragmentation of the global trading system. After 2020, international trade has undergone significant structural changes, driven by the COVID-19 pandemic, geopolitical conflicts, technological transformation, and the activation of industrial policy. In these conditions, economic diplomacy is becoming a key mechanism for coordinating foreign economic, security and innovation priorities of states. The purpose of the article is a comprehensive analysis of the transformation of economic diplomacy tools in the context of intensifying international competition and assessing their impact on the functioning of the modern trading system. The methodological basis of the study is comparative and structural-functional methods of analysis, as well as systematization of data from the World Trade Organization, the UN Comtrade database, and Global Trade Alert. The study revealed an increasing role of selective liberalization, an increased use of protective and compensatory measures, the intensification of industrial policy, and the expansion of regulatory influence in the field of digital services and intellectual property. It is established that the combination of trade, industrial and technological instruments contributes to the formation of new models of international competition and increases the asymmetry of development between countries. The importance of integrating economic diplomacy with long-term strategies of innovative and digital development is substantiated. The practical value of the results lies in their use by state administration bodies, diplomatic institutions, and entities of foreign economic activity to develop effective strategies for international cooperation, minimize trade risks, and increase the competitiveness of the national economy. The results obtained can be used in the process of shaping national foreign economic policy, improving mechanisms of international cooperation, and developing strategies to adapt to changes in the global economic environment.